The mudharabah deposit rate behaviour in relation to the conventional deposit rate - Radziah Abdul Latiff; Noreha Halid (Penerbit Universiti Kebangsaan Malaysia, 2012)

(untitled)
This study examines the relationship between the conventional and mudharabah deposit rates of Malaysian banks in two separate periods — between January 1996 and September 2004, and between October 2004 and June 2011 — which signify the implementation of a framework for calculating the Islamic bank deposit rate and the profit equalization reserve (PER). Employing the autoregressive distributed lagged (ARDL) approach, this study finds the two rates to be cointegrated in the first period similar to previous findings. However, for the second period, there is largely no evidence of a long-term relationship. The significance of this finding is that in the second period, when Islamic banks employ a regulated PER as a displacement risk mitigating mechanism, Islamic banks do not benchmark against conventional rates. They possibly engage in income smoothing for economic efficiency or for signalling purposes. An important policy implication is that PER and any type of reserve to smooth income, that is regulated, may be prescribed as it may have a positive behavioural effect.